Antibacterial Activity of Tulsi Ethanolic Extract (Ocimum tenuiflorum L.) against Staphylococcus aureus - I Gusti Ngurah Kezawa Arisurya; Pande Ayu Naya Kasih Permatananda; Ni Wayan Erly Sintya Dewi; I Gde Suranaya Pandit (Postgraduate, University of Mataram, 2026)
Infectious disease is a type of disease caused by invasion by microbiological agents, such as bacteria. One type of bacteria is Staphylococcus aureus which is a Gram-positive bacteria. The definitive therapy for bacterial infections is the administration of antibiotics. However, overuse of antibiotics leads to bacterial resistance. One of the efforts to overcome this is with alternative antibiotics made from herbs, such as Tulsi (Ocimum tenuiflorum L.). This study aims to determine the antibacterial activity of Tulsi ethanolic extract against S. aureus. This research was conducted at the Analysis Laboratory of the Faculty of Agriculture, Warmadewa University from October to November 2024. The research design used a true experimental method with a posttest only control group design model, namely by testing the antibacterial activity of Tulsi ethanolic extract with concentrations of 25%, 50%, and 75% against S. aureus. In the antibacterial test results, the diameter of the inhibition zone formed at concentrations of 25%, 50%, and 75% was 5.25 mm, 5.90 mm, and 7.22 mm, respectively. Based on the One Way ANOVA test results, the P value <0.001 was obtained, which means there is a significant difference between the treatment groups. Based on this study, it can be concluded that Tulsi ethanolic extract has moderate antibacterial activity.